Arteriovenous fistula of the superior gluteal artery as a complication of posterior iliac crest bone graft harvesting: 3D-CT angiography and arterial embolization - Kong, Chae-Gwan (Springer-Verlag, 2009)
Superior gluteal artery injuries are rare, but potentially serious complications that occur during posterior iliac crest bone graft harvesting. The authors reported an arteriovenous fistula of the superior gluteal artery, which occurred as a complication during posterior iliac crest bone graft harvesting and was diagnosed with 3D-CT angiography, then treated with arterial embolization.